Ecofriendly pest management for food security - Omkar (London, UK : Academic Press, 2016)
Ecofriendly Pest Management for Food Security explores the broad range of opportunity and challenges afforded by Integrated Pest Management systems. The book focuses on the insect resistance that has developed as a result of pest control chemicals, and how new methods of environmentally complementary pest control can be used to suppress harmful organisms while protecting the soil, plants, and air around them.As the world's population continues its rapid increase, this book addresses the production of cereals, vegetables, fruits, and other foods and their subsequent demand increase. Traditional means of food crop production face proven limitations and increasing research is turning to alternative means of crop growth and protection.
Insects and pests -- Biocontrol of insect pests -- Aphids and their biocontrol -- Parasitoids -- Trichogrammatids -- Anthocorid predators -- Reduviid predators -- Syrphid flies (the hovering agents) -- Ladybird beetles -- Chrysopids -- Mite predators -- Entomopathogenic Nematodes -- Insect viruses -- Bacillus thuringiensis -- Entomopathogenic Fungi -- Plant monoterpenoids (prospective pesticides) --Antifeedant phytochemicals in insect management (so close yet so far) -- Neem products -- Semiochemicals -- Insect hormones (as pesticides) -- Integrated pest management -- Biotechnological approaches -- GMO and food security.
Includes bibliographical references and index.
Print version record.
Keywords: Pests -- Control -- Environmental aspects; Food security; TECHNOLOGY & ENGINEERING -- Environmental -- General; Food security; Pests -- Control -- Environmental aspects; Electronic books; Electronic books